Optimal policy under dollar pricing - Konstantin Egorov; Dmitry Mukhin (Leibniz Institute for Financial Research SAFE, 2023)
Recent empirical evidence shows that most international prices are sticky in dollars. This paper studies the policy implications of this fact in the context of an open economy model, allowing for an arbitrary structure of asset markets, general preferences and technologies, time- or state-dependent price setting, and a rich set of shocks. We show that although monetary policy is less eftcient and cannot implement the flexible-price allocation, inflation targeting and a floating exchange rate remain robustly optimal in non-U.S. economies. The capital controls cannot unilaterally improve the allocation and are useful only when coordinated across countries. Thanks to the dominance of the dollar, the U.S. can extract rents in international goods and asset markets and enjoy a higher welfare than other economies. Although international cooperation beneffts other countries by improving global demand for dollar-invoiced goods, it is not in the self-interest of the U.S. and may be hard to sustain.
Keywords: 330